Enfrichement des côtes rocheuses : analyse de la dynamique du paysage et de la végétation - Pierre Libaud; Jérôme Sawtschuk (M@ppemonde)
This study examines two coastal post-agricultural lands of the commune of Moëlan-sur-Mer affected by a recultivation project. It aims to interrogate the landscape heterogeneity and specific diversity of these abandoned lands and their nearby areas. The analysis of landscape dynamics since the 1950s suggests several rhythms and trajectories, depending on the areas, anthropic action and ecological constraints. The results show a diversity of vegetation types and multiple trajectories, challenging the idea of a landscape homogeneization of coastal post-agricultural lands.